Physiological quality of pink pepper seeds (Schinus terebinthifolia Raddi.) as a function of storage - Silveira, Thaísa de Oliveira; Braz, Madelon Rodrigues; Palermo, Gilmara Pires de Moura; Breier, Tiago Böer (Revista de Ciencias Agrícolas, 2021)
Seeds of native forest species for food and seedling production have a growing demand that impacts the need for studies involving seed storage in order to maintain good levels of germination quality. Thus, scientific analyzes that explore the physiological potential of the seeds of these species are necessary, especially for the pink pepper (Schinus terebinthifolia Raddi.), a species used as an alternative source of income for traditional communities and which has been arousing interest due to the consumption of its fruits as a condiment in the national and international market. This work aimed to assess the physiological quality of pink pepper seeds according to the storage period and seed size. The seeds came from a rural settlement, a pioneer in the extraction of pink pepper, in the state of Rio de Janeiro, Brazil. The seeds were evaluated for moisture content, germination, first count, length and dry weight of the germinated seedlings, during the period of time that they remained stored and the size of the seeds. The results allowed to conclude that: i) the germinative percentage of the stored pink pepper seeds decreased over the months; ii) the moisture content of the seeds decreased over the months evaluated iii) the different sizes of seeds did not show differences in germination and storage time and iv) values of length and dry weight of the seedlings did not differ according to the period of storage.